Sistem Informasi Penerimaan Peserta Didik Baru Online Berbasis Website di Yayasan Pendidikan Arya Jaya Sentika - Taufik Hidayat; Mahmudin Muttaqin; Djamaludin Djamaludin (Komputika : Jurnal Sistem Komputer, 2020)
Acceptance of New Students is the first step in the management of school services to the community in education. how the school promotes products and at the same time excellent service begins with the acceptance of students, and then students or parents will get access to the portal. This research uses the waterfall method in designing information systems for admission of new students, the waterfall method is a method which is the design of the System Development Life Cycle (SDLC), where design begins with requirements, design, implementation, verification and maintenance. Data collection techniques through field observations, interviews, and literature studies. PHP (HyperText Markup Language) is a server-side website based programming language, it means that the PHP program code is processed entirely on the web server. MySQL is a language that has good ability to support the work of developers, uncluding for users experienced with databases and for beginners. A new online student-based website admission information system will help facilitate data and information communication between parents of prospective students and educional institutions. Application test results show the level of need for a new site-based online student acceptance information system touched 78% value.